REPRESENTATION OF CULTURE ECOLOGY IN WISRAN HADI’S PERSIDEN, GENERASI KETUJUH - Sugiarti Sugiarti; Candra Rahma Wijaya Putra (LITERA, 2019)
Culture and humans are interdependent and fused by ecological processes and natural energy cycles. The author as the creator of the work cannot be separated from the cultural environment from which it originates. This study aims to reveal (1) cultural elements and (2) representation of cultural ecology in the novel. The material object of this study is Wisran Hadi's Persiden, Generasi Ketujuh novel. The uses a qualitative descriptive method that describes the research subject based on the facts of the visible cultural ecology. Data analysis of the study is done by classifying data, categorizing data, and finding important issues related to the study of cultural ecology. In addition, it is also supported by interactive-dialectical analysis or back and forth to track the overall findings. The results of the study reveal that (1) the universal element of culture (cultural system) is the basis for discussion of cultural ecology. The cultural system is very dominant and even becomes the author's frame of mind in presenting the reality of life in his work. The strengths and relations built by each system represent the operation of cultural ecology in literature; (2) cultural ecology can be considered through a shift in people's mindsets in adapting to their environment. This adaptation has implications for the division of community groups into two. First, one community makes adaptation by maintaining local identity, namely tradition. Second, other societies make adaptation by leaving the tradition to the modern (global) trend. Keywords: culture ecology, elements of culture, adaptation